Angiotensin II type 1-receptor mediated changes in heparan sulfate proteoglycans in human SV40 transformed podocytes - Brinkkötter, Paul-Thomas; Holtgrefe, Simone; Woude, Fokko J. van der; Yard, Benito A. (Journal of the American Society of Nephrology, 2004)
In patients with diabetic nephropathy, glomerular staining for heparan sulfate proteoglycans (HSPG) side chains and for agrin is decreased. In the present study, the influence of angiotensin II (AngII) on the production of HSPG in SV40 transformed podocytes was investigated. SV40 transformed human podocytes were cultivated with or without 1 microM AngII, and HSPG production was measured by sequential DEAE-anion exchange chromatography and HPLC-DEAE separation. Expression of agrin was studied by indirect immunofluorescence and Western blot analysis using specific mono- and polyclonal antibodies. DEAE separation of total glycosaminoglycans (GAG) revealed a significant increase of GAG in the culture supernatant and decrease in the cell and matrix layer when podocytes were cultured for 72 h in the presence of AngII. This was particularly found for HS-GAG. Qualitative analysis of HSPG, using gel filtration of HNO(2)-treated fractions, showed that AngII treatment decreased N-sulfation of HS-GAG side chains. Indirect immunofluorescence staining with anti-agrin polyclonal antibody was strongly decreased after AngII stimulation. A reduction in agrin expression in cell extracts could also be detected in Western blot analysis using an mAb. No changes in agrin mRNA were found after AngII stimulation. It is concluded from this study that AngII decreases the amount of HSPG on the cell surface and in the extracellular matrix of podocytes. Because HSPG play a fundamental role in the permselectivity of the glomerular basement membrane, these results thus may explain at least partially the antiproteinuric effects of angiotensin-converting enzyme inhibition in patients with diabetic nephropathy.
Gesehen am 02.06.2022